1983
DOI: 10.1115/1.3225654
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependence in Biaxial Yield of Type 316 Stainless Steel at Room Temperature

Abstract: This paper describes two biaxial experiments which investigated time and rate effects in the yield and deformation behavior of type 316 stainless steel at room temperature. The first experiment was aimed at determining the effect of probing rate on small-offset yield behavior. The primary aim of the second experiment was to investigate time-dependent flow after loading beyond initial yield. An additional aim was to investigate the effect of radial (3 σ12 = σ11) and nonradial preloads on the yield and hardening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There were also experimental results which showed contraction first and then expansion with increasing plastic pre-strains (Helling et al, 1986;Shiratori et al, 1973;Williams and Svensson, 1971). More information about the evolution of yield surface was reported in Ellis et al (1983), Boucher et al (1995), Lissenden and Lei (2004), and in the book (Wu, 2005).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…There were also experimental results which showed contraction first and then expansion with increasing plastic pre-strains (Helling et al, 1986;Shiratori et al, 1973;Williams and Svensson, 1971). More information about the evolution of yield surface was reported in Ellis et al (1983), Boucher et al (1995), Lissenden and Lei (2004), and in the book (Wu, 2005).…”
Section: Introductionmentioning
confidence: 87%
“…In probing yield surfaces, the strain rates were about _ e zz ¼ 2 Â 10 À6 s À1 and _ c ¼ 2 _ e zh ¼ 5:5 Â 10 À6 s À1 . Note that it was mentioned by Ellis et al (1983) and Wu and Yeh (1991) that the probing rate had little effect on the yield surface determination. This automated process of yield stress determination required less manipulation by the operator and it had higher efficiency and decreased artificial errors.…”
Section: An Automated Yield Stress Determinationmentioning
confidence: 94%
“…A magnification of several loading‐unloading cycles (N) is represented in Figure b, where the maximum deformation takes place for the initial P‐h cycles; when the indentation cycle increases, the aperture of the P‐h cycles decreases. This effect has been previously appreciated under conventional dynamic tests at the macroscopic length scale, which is mainly attributed to the ratcheting strain accumulation effect. Within this context, the open loops for low cyclic cycles observed in Figure b, may be described because of increasing the dislocation activity during the indentation process.…”
Section: Resultsmentioning
confidence: 68%
“…Crystal orientation in the region where the micromechanical properties were loading sequence, remaining thus significant amount of dislocations in the substructure which cause the increase in dislocation density [19]. This phenomenon, also known as ratcheting strain accumulation effect, has been previously observed for austenitic stainless steels under conventional fatigue testing, as reported elsewhere [15,17,20,21,22,23]. Misra et al [24] found the same trend described above at the local scale by using the nanoindentation technique for austenitic grains, whereas the loops for the martensite phase were close.…”
Section: Crystallographic and Deformation Mechanisms Characterizationmentioning
confidence: 53%